Comércio exterior e relações internacionais: uma visão neointitucionalista do peiex no Tocantins - Dutra, Anna Beatriz Theophilo (Universidade Federal do Tocantins, 2023)
With the constant evolution of the commercial market, the challenges for the national sectors are to keep up with technological development and remain competitive internationally. It is visible, through the database made available by the chambers of commerce, that the focus of exports today are products without added value. Talking about exports within small companies raises the degree of anxiety of entrepreneurs, because there is a preconception that it is only possible for fully structured companies, with high production. Besides being a difficult, expensive, and bureaucratic process. The aim of this work is to demonstrate the effectiveness of PEIEX as a helper to enter the international market. The present work discusses the low quantitative numbers of exports of manufactured products in the state of Tocantins, thus creating a problem about the industrialization of the state and aims to solve this deficit with the Export Qualification Program - PEIEX. In this way, to reach such a conclusion, the following construction of the work is present: (a) presentation of the theory that supports the institutions that aim to provide support in the foreign market onslaught - neoinstitutionalism; (b) conceptualizes foreign trade and international trade; (c) sequencedby an analysis of the Brazilian and Tocantins trade balance, which indicates the need for the incentive since the export numbers are still too low; (d) finally, descriptively presents the program and justifies the implementation of PEIEX in the state of Tocantins.